Spatial occurrence-intensity modeling of dengue incidence in southernmost provinces of Thailand. - Apiradee Lim; Lumpoo Ammatawiyanon; Haris Khurram; Phattrawan Tongkumchum; Don McNeil (PLoS Neglected Tropical Diseases, 2025)
Background Dengue is currently spreading and is considered a hyperendemic in Thailand. Outbreaks happen almost every year in various provinces of Thailand, especially the four southernmost provinces consistently reporting for more than a decade. This study aimed to explore the spatial distribution and high-risk areas using an occurrence-intensity model at a sub-district level in the four southernmost provinces of Thailand. Methods The record of the cases admitted to the hospital and diagnosed as dengue in the 377 sub-districts of four southernmost provinces, Songkhla, Pattani, Yala, and Narathiwat from 2008 to 2020, gender-age wise, were taken from the Office of Disease Prevention and Control, Ministry of Public Health, Thailand. We suggested a methodology based on the occurrence-intensity model to analyze the dengue cases in two steps. At first, the occurrence is determined by using the logistic regression model and considering the variable of interest as a case or not. While at second, the intensity is determined by fitting a log-linear regression model for disease intensity after excluding zeros. Results The results from 78,416 observations revealed that a total number of 68,526 dengue cases were registered from 2008-2020 in all four southernmost provinces. The overall average occurrence rate was 28.3% while the average intensity was 419 per 100,000 population. The occurrence-intensity model gives a much better fit to the data and highlights that the gender-age patterns of occurrence and intensity are different. Occurrence is higher among young adult ages and then declines with age for each gender, whereas intensity is higher in children, young adults, and the elderly for each gender. The sub-districts are in the suburbs of the Songkhla province and sporadically, areas on the border of the Narathiwat province had high occurrence and intensity. Conclusions The spatial occurrence and intensity of dengue in sub-districts can provide valuable guidance to identify high-risk areas and monitor the intensity of dengue cases in these areas. This will be useful for healthcare departments in developing effective public health strategies for dengue control.